Hubungan Antara Lama Penggunaan Kontrasepsi Suntik Depo Medroxyprogesterone Acetate Dengan Peningkatan Berat Badan Akseptor Di Praktik Mandiri Bidan HS Denpasar Barat Tahun 2019 - Devi Noviantari; Ni Gusti Kompiang Sriasih; Juliana Mauliku (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2019)
Current contraceptive use is dominated by short-term contraceptives, especially injection contraception. Injected contraception medroxyprogesterone acetate (DMPA) is a hormonal contraceptive containing progestins that stimulates the hypothalamus to trigger appetite which results in increased body weight. This study aims to determine the relationship between the duration of injection contraceptive use and the increase in acceptor body weight. The study was carried out in Clinic of Midwifery “HS” with a sample of 60 DMPA acceptors with more than one year of use. The type of this research is observational analytic with cross sectional design, by way of approach to the subject of research is a retrospective. The results of the research conducted in Clinic of Midwifery “HS” found that all DMPA contraceptive respondents gained weight. Statistical tests using the Spearman Rank test obtained p-value which is 0.000. The relationship between duration of depot injection contraceptive use medroxyprogesterone acetate and the increase in acceptor body weight, it is expected that midwives can provide counseling about the side effects of DMPA contraceptive use so that they can intervene to handle it.